Ownership, Intellectual Capital, Audit Quality, Debt Level and Integrity of Financial Statements - Afrilia, Widiawati Dwi; Surifah, Surifah (Jurnal Manajemen, 2023)
There are many cases of financial statement manipulation in practice which result in low financial statement integrity, unreliability and can mislead users. Therefore, research on the financial statement integrity (FSI), especially in the consumer goods industry, is important to study. This research aims to provide evidence of the effect of ownership type, intellectual capital, audit quality and debt levels on the integrity of the financial statements of the consumer goods manufacturing industry in companies listed on the Indonesia Stock Exchange. Sample of this research is consumer goods manufacturing companies listed on the IDX. The six sub-sectors of the consumer goods industry are food and beverages, pharmaceuticals, cigarettes, cosmetics and household goods, household appliances and other consumer goods. The purposive sampling method was used to select the sample. The number of samples observed was 249 during 2017-2021. The analysis technique uses multiple regression tests. The results showed that domestic institutional ownership, foreign institutional ownership, government institusional ownership had a positive and significant effect on the FSI. Debt level and quality of audit proved to have a negative and significant effect on FSI. Individual ownership and intellectual capital had no effect on the FSI. This research differentiates into 4 types of ownership, namely domestic, foreign, government, and individual ownership. It is still rare to research that distinguishes the 4 types of ownership. In addition, research specifically using consumer goods industry samples is still rare, even though there are cases of low financial report integrity in this industry.